Analysing Long-Term Care for Rural Older Adults: A Bibliometric Synthesis: Review Article. - Acero, Álvaro Elices; Prieto-Lobato, Juan María; Rodríguez-Sumaza, Carmen (Ageing International, 2025)
The ageing population is a complex demographic process, and its implications for care have become a major global social issue. As the needs for care increase and grow longer in time, the challenges facing protection systems intensify. Living in rural areas is often an added difficulty in the access of older adults to care services. At this crossroads, the role of science is essential to articulate innovative, effective, and sustainable responses, from the approach of evidence-based practice. To undertake a review of the literature on long-term care for older adults living in rural areas, a bibliometric analysis (using VOSviewer and CiteSpace software) and a thematic synthesis have been conducted on 372 scientific articles. A growing interest in research on the subject is identified through the progressive increase in the number of publications. The study also reveals an evolution of scientific interest going from care that is biomedical in nature, centred in situations of dependency, to approaches inspired by person-centred care, focused on promoting autonomy. It is also noted that international collaborations are limited and studies do not often analyse the gender issue, which is key in both formal and informal care systems. This study aims to be a reference work for researchers, academics, practitioners and policymakers by offering a broad analysis of the state of the science on its subject.